Assessing the Performance of Low Pressure Distribution Irrigation Systems Using the Labye's Iterative Discontinuous Method - Pereira L.S.; Douieb A.; Bounoua R.; Lamaddalena N.; Calejo M.J. (Annual Meeting of the Mediterranean Network on Collective Irrigation Systems (CIS_Net), 2000)
Low pressure irrigation distribution systems for surface irrigation provide for recognized environmental benefits qt both off- and on-farm. However, expected benefits can only be attained when design provides for appropriate systems performance and adequate water use at farm. An innovative methodology for analysis and design is proposed, which includes the generation of farm demand and flow regimes for the peak demand period, the optimisation of pipe sizes using the Labye's iterative discontinuous method, and the performance analysis from simulations with several flow regimes. An application to one sector of the Sorraia irrigation system illustrates the method proposed.
Proceedings of the Annual Meeting of the Mediterranean Network on Collective Irrigation Systems (CIS_Net), 1999/11/03-06, [sl] (Malta)